Contrasting Changes in Diel Variations of Net Community Calcification Support That Carbonate Dissolution Can Be More Sensitive to Ocean Acidification Than Coral Calcification - Chou, Wen-Chen; Liu, Pi-Jen; Chen, Ying-Hsuan; Huang, Wei-Jen (Frontiers in Marine Science, 2020)
Previous studies have found that calcification in coral reefs is generally stronger during the day, whereas dissolution is prevalent at night. On the basis of these contrasting patterns, the diel variations of net community calcification (NCC) were monitored to examine the relative sensitivity of CaCO3 production (calcification) and dissolution in coral reefs to ocean acidification (OA), using two mesocosms that replicated a typical subtropical coral reef ecosystem in southern Taiwan. The results revealed that the daytime NCC remained unchanged, whereas the nighttime NCC decreased between the control (ambient) and treatment (OA) conditions, suggesting that carbonate dissolution could be more sensitive to OA than coral calcification. The average sensitivity of the integrated daily NCC to changes in the seawater saturation state (a) was estimated to be a reduction of 54% in NCC per unit change in a, which is consistent with the global average. In summary, our results support the prevailing anticipation that OA would lead to a reduction in the overall accretion of coral reef ecosystems. However, increased CaCO3 dissolution rather than decreased coral calcification could be the dominant driving force responsible for this OA-induced reduction in NCC.